ANALISISRENCANAPELAKSANAANPEMBELAJARAN (RPP)BIOLOGI BERKARAKTER KELAS XISMAN UNTUKSTANDARISASI RPP DI KAB. TANAH DATAR - Santi, Widya; Risdawati, Renny; Mulyati, Mulyati (STKIP PGRI Sumbar, 2013)
ABSTRACTÂ Lesson Plan (RPP) is essentially a plan that describes the procedures to achieve a learning organization specific competencies. To find out standardization Lesson Plan (RPP) is to the lesson Plan (RPP) biology class at eleventhSMAN Tanah Datar regency with IPKG-1. The purpose of this research was to determine the relationship between the standardization of RPPand RPP components made by biology teachers ofSMAN semester classes in Tanah Datar.This research is a descriptive study by collecting lesson plans from classroom biology teacher at SMAN Tanah Datar. This sampling technique is Stratifed Random Sampling. The result of analysis we found that the Lesson Plan (RPP) biology class in SMAN Tanah Datar on standard criteria.Â Â